2021
DOI: 10.3390/microorganisms9030543
|View full text |Cite
|
Sign up to set email alerts
|

Human Skin Microbiome: Impact of Intrinsic and Extrinsic Factors on Skin Microbiota

Abstract: The skin is the largest organ of the human body and it protects the body from the external environment. It has become the topic of interest of researchers from various scientific fields. Microorganisms ensure the proper functioning of the skin. Of great importance, are the mutual relations between such microorganisms and their responses to environmental impacts, as dysbiosis may contribute to serious skin diseases. Molecular methods, used for microorganism identification, allow us to gain a better understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(165 citation statements)
references
References 123 publications
(146 reference statements)
2
108
1
10
Order By: Relevance
“…can be found. The biodiversity of microbiota is generally decreased in moderate-to-severe psoriatic patients in contrary to mild psoriatic patients [5].…”
Section: Psoriasismentioning
confidence: 94%
See 2 more Smart Citations
“…can be found. The biodiversity of microbiota is generally decreased in moderate-to-severe psoriatic patients in contrary to mild psoriatic patients [5].…”
Section: Psoriasismentioning
confidence: 94%
“…They can be found not only on the surface of the epidermis, but also in sweat, sebaceous glands and associated hair follicles [4]. The composition of microbiome differs among different regions affected by numerous factors including age, gender, genetics, immunity, hormonal balance, sleep routine, stress, metabolic factors, hygiene and skin care routine, chemical or ultraviolet radiation exposure, physical activity, climate, environmental pollution and availability of nutrients [5]. The initial colonization of the skin depends on the delivery mode, with neonates delivered vaginally acquiring the species (spp.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin's surface is dry and acidic, with a pH of around 4.1 to 5.8 [20]. The top layer of the epidermis continuously releases 600,000−1,000,000 keratinized cells per hour for renewal of the skin every month [21]. It has been reported that about 10% of exfoliated cells are composed of bacteria that affect the skin microbiota's composition [22].…”
Section: Cutaneous Microbiomementioning
confidence: 99%
“…Although the picture of microbial dysbiosis is currently incomplete (particularly whether it is a cause or consequence of disease [ 77 ]), work thus far indicates that microbe biodiversity and abundance, influenced by host or intrinsic factors (e.g., age, gender, immunity and hormonal status) [ 78 , 79 ] and environmental or extrinsic factors (e.g., climate, physical activity, diet, grooming products or even face mask wearing as highlighted during the recent COVID-19 pandemic) [ 14 , 80 ], are important in maintaining skin health or driving disease. The microbial component of disease has therefore been an important target in treatment with anti-fungal therapies such as the commercially popular ZnPT available over-the-counter.…”
Section: Microbial Dysbiosis As a Key Target For Treatmentmentioning
confidence: 99%